Fundamentals of power systems - Banerjee, B.; Jayaweera, D.; Islam, Syed (2016)
© Springer International Publishing Switzerland 2016. The chapter describes the history, evolution, and fundamental analysis frameworks of a power system. Power systems started modestly as small scale DC systems. As the dependence on electricity has increased, the complexities and demands placed on electricity have also been increased. The chapter begins with a description of the history of power systems and then describes major events that have shaped the modern power system industry. A description of the basic power system components are presented along with analysis techniques of load flow, optimal power dispatch, and transient stability. The chapter fundamentals will aid in a better understanding of the remaining chapters.